Financial Planning: Applications To “Mining Contractors Services Company” In Indonesia - Jacky Maitimu; Rhian Indradewa (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Background – PT ANP is a mining service company in Indonesia. startup companies in running the PT ANP mining services business really need to carry out financial analysis by calculating and analyzing existing parameters. The data obtained from this analysis will be able to assist company management in making strategic decisions both now and in the future. One such analysis is the investment feasibility analysis. In addition, a method for assessing the feasibility of an investment is also needed in identifying prospects for an investment plan. The prospect of an investment plan can be used as a basis for making decisions to accept or reject an unprofitable investment. Financial planning is an important aspect for the sustainability of PT ANP's mining services business. Method – Using financial plan framework Result – This financial analysis can help companies in financial decisions.